(untitled) (gjstudies, 2022)
This research introduces a novel methodological framework for evaluating the effectiveness of risk disclosures related to financial instruments, moving beyond traditional contentanalysis to incorporate computational linguistics, network analysis of disclosure interdependencies, and behavioral finance constructs. Traditional accounting research has predominantly focused on compliance with disclosure standards (IFRS 7, IFRS 9) and the volume ofinformation provided, often neglecting the cognitive accessibility, contextual relevance, anddecision-usefulness of disclosed content for heterogeneous user groups. Our study posits thatdisclosure effectiveness is not a linear function of quantity but a multidimensional constructinvolving clarity, connectivity, forward-looking orientation, and risk materiality articulation.We develop and validate the Financial Instrument Disclosure Effectiveness (FIDE) Index, acomposite metric derived from machine learning-based text analysis of annual reports from150 global financial institutions over a five-year period, paired with experimental studiesinvolving investment analysts and non-professional investors. The methodology uniquelyintegrates semantic coherence scoring, sentiment trajectory analysis across risk narratives,and graph-based mapping of risk interlinkages disclosed. Results demonstrate a significant,non-uniform gap between regulatory compliance and genuine communicative effectiveness,with key findings indicating that overly technical and fragmented risk disclosures, while compliant, can obfuscate material risk exposures rather than illuminate them. Furthermore, weidentify a ’disclosure complexity paradox,’ where institutions with the most complex financialinstrument portfolios tend to produce disclosures that score lowest on cognitive accessibilitymetrics, potentially exacerbating information asymmetry. The paper concludes by proposing a principles-based supplement to existing standards, emphasizing dynamic, user-centricdisclosure design. This research contributes original insights to accounting, risk communication, and financial regulation by reframing disclosure effectiveness as a human-computerinteraction and behavioral communication challenge, rather than solely a compliance exercise.